New fishfly species of the Neochauliodes bowringi group (Megaloptera: Corydalidae: Chauliodinae) - Jiang, Wei; Wang, Guoquan; Liu, Xingyue (Zootaxa, 2012)
Two new species of the fishfly genus Neochauliodes from Cambodia and China are described and both of them belong to the Neochauliodes bowringi species group. A key to the males of the N. bowringi group is also given.